None greater : the undomesticated attributes of God - Barrett, Matthew, 1982- (Grand Rapids, Michigan : Baker Books, a division of Baker Publishing Group, 2019)
"Author and theologian helps readers get to know a God who is much bigger than we ever imagined by explaining his attributes in a way that highlights their relevance and impact on the Christian life"--
Is God incomprehensible? no one can know the essence of God -- Can we think God's thoughts after him? how the creature should (and should not) talk about the Creator -- Is God the perfect being? why an infinite God has no limitations -- Does God depend on you? Aseity -- Is God made up of parts?: simplicity -- Does God change? immutability -- Does God have emotions? impassibility -- Is God in time? timeless eternity -- Is God bound by space? omnipresence -- Is God all-powerful, all-knowing, and all-wise? omnipotence, omniscience, and omnisapience -- Can God be both holy and loving? righteousness and goodness -- Should God be jealous for his own glory?.
Includes bibliographical references (pages 273-283).
Keywords: God (Christianity) -- Attributes